2018
DOI: 10.1186/s10194-018-0867-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the trigeminovascular actions of several adenosine A2A receptor antagonists in an in vivo rat model of migraine

Abstract: BackgroundMigraine is considered a neurovascular disorder, but its pathophysiological mechanisms are not yet fully understood. Adenosine has been shown to increase in plasma during migraine attacks and to induce vasodilation in several blood vessels; however, it remains unknown whether adenosine can interact with the trigeminovascular system. Moreover, caffeine, a non-selective adenosine receptor antagonist, is included in many over the counter anti-headache/migraine treatments.MethodsThis study used the rat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Like other analgesics (55), caffeine increases dopamine release (18), probably via inhibition of A 2A R (56). Notably, A 2A receptor antagonists did not affect dural meningeal vasodilatation caused by CGRP in a rat model (57). The recent marketing of CGRP receptor antibodies and the development of CGRP antagonists has been considered a major breakthrough in the migraine field (58).…”
Section: Resultsmentioning
confidence: 99%
“…Like other analgesics (55), caffeine increases dopamine release (18), probably via inhibition of A 2A R (56). Notably, A 2A receptor antagonists did not affect dural meningeal vasodilatation caused by CGRP in a rat model (57). The recent marketing of CGRP receptor antibodies and the development of CGRP antagonists has been considered a major breakthrough in the migraine field (58).…”
Section: Resultsmentioning
confidence: 99%
“…Fried et al ( 32 ) suggested that it is the adenosine receptor A2A signaling that contribute to headache via modulation of intracellular cyclic adenosine monophosphate (cAMP) in neurons and glia to subsequently affect glutaminergic synaptic signaling. Based on an in vivo rat model of migraine, ( 39 ) suggested that A2A receptor antagonism may offer a novel approach to antimigraine therapy. Imaging studies using positron emission tomography (PET) A1AR- ( 31 ) and A2AR-ligands are suitable for studying the cerebral effects of caffeine ( 40 ), and may perhaps also be suitable for studying the effects of caffeine withdrawal as a trigger for migraine in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, adenosine application to the rodent isolated middle meningeal artery exerts vasodilation, which is considered one of the triggering events for a migraine attack (Haanes & Edvinsson, 2014). This effect is observed also in living animals thanks to in vivo videomicroscopy and is blocked by selective A2A receptor antagonists and by caffeine, a non-selective adenosine receptor antagonist, which is often included in over-the-counter drugs for acute migraine attacks (Haanes et al 2018). Thus, the modulation of cerebral vessel diameter through A2A receptors can be one of the mechanisms through which caffeine contribute to reduce migraine and headache attacks.…”
Section: Adenosine and P2y Receptors In Inflammatory Pain And In Migrmentioning
confidence: 99%
“…In the field of adenosine-mediated signaling, some of the above-mentioned problems have now started to be solved, thanks to the invaluable efforts of medicinal chemists. New selective and potent A3 adenosine receptor agonists are now available , new A1 receptor agonists devoid of any cardiac actions have been designed and tested as analgesic agents (Petrelli et al, 2017;2018), and new selective A2A receptor antagonists acting as vasodilators in migraine are currently under development (Haanes et al, 2018). When dealing with adenosine agonists, an important issue to be considered is represented by the massive (ab)use of the methylxanthine caffeine, which acts as antagonist at various adenosine receptor subtype and could therefore alter the results of clinical trials and, prospectively, the beneficial effects of any agonist which will reach the market (Chen et al, 2013).…”
Section: When Will a Purinergic-based Drug Reach The Market As Innovamentioning
confidence: 99%